Microstructure and mechanical properties of gas metal arc welded CoCrFeMnNi joints using a 410 stainless steel filler metal - Shen, Jiajia (2022)
Funding Information: JS, JGL and JPO acknowledge Fundação para a Ciência e a Tecnologia (FCT - MCTES ) for its financial support via the project UID/00667/2020 ( UNIDEMI ). JPO acknowledges the funding of CENIMAT/i3N by national funds through the FCT-Fundação para a Ciência e a Tecnologia , I.P., within the scope of Multiannual Financing of R&D Units , reference UIDB/50025/2020-2023 . JS acknowledges the China Scholarship Council for funding the Ph.D. grant ( CSC NO. 201808320394 ). This work was supported by the National Research Foundation of Korea (NRF) with a grant funded by the Korea government ( MSIP ) ( NRF-2021R1A2C3006662 ). The authors acknowledge DESY (Hamburg, Germany), a member of the Helmholtz Association HGF, for the provision of experimental facilities. Beamtime was allocated for proposal I-20210899 EC. Publisher Copyright: © 2022 The Authors